Multi-omics analysis elucidates the therapeutic mechanisms of the Quzhi formula in metabolic dysfunction-associated steatohepatitis targeting gut microbiota, lipid metabolism, and the role of its metabolite fraxin - Wu, Jiao-Xiang; Wu, Yue-Lan; Li, Mei-Fang; Liu, Nian; Liu, Ying; Huang, Yan-Ping; Gan, Yuan; Wang, Xiao-Yu; Chai, Hai-Sheng; Xu, Jin; Xi, Qian; Guo, Xi-Rong; et al. (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated steatohepatitis (MASH) is an advanced stage of fatty liver disease with no approved pharmacotherapies. The Quzhi Formula (QZF), a traditional Chinese medicine utilized clinically for nearly two decades, has shown promising efficacy against MASH; however, its mechanisms of action remain largely unexplored. To elucidate these mechanisms, we conducted a multi-omics investigation integrating 16S rRNA sequencing, untargeted metabolomics, and transcriptomics in a MASH mouse model, with findings validated by histology. QZF treatment significantly alleviated hepatic steatosis, restored gut microbial diversity, and suppressed the proliferation of Enterococcus, a genus implicated in MASH pathogenesis. Transcriptomic and metabolomic analyses demonstrated that QZF’s therapeutic effects were mediated through the regulation of lipid metabolic pathways and the activation of autophagy. Furthermore, we identified fraxin as a pivotal bioactive metabolite contributing to QZF-induced autophagy. Our study demonstrates that QZF ameliorates MASH in a concerted manner by remodeling the gut microbiota, reprogramming hepatic metabolism, and promoting autophagy via fraxin. These results provide a comprehensive mechanistic foundation for QZF as a multi-targeted therapeutic candidate for MASH.